The roles of men and women in maternal and child nutrition in urban South Africa: A qualitative secondary analysis - Agnes Erzse; Susan Goldstein; Aviva Tugendhaft; Shane A. Norris; Mary Barker; Karen J. Hofman; for the INPreP group (Wiley, 2021)
Abstract Industrialization and urbanization processes have challenged deeply held traditional gender norms and facilitated the emergence of modern ideologies in South Africa. This paper seeks to explore the gendered roles of family members on maternal and child nutrition and investigate indications of perceived change in related practices. A qualitative secondary analysis was conducted of data from nine focus group discussions (FGDs) held with men (n = 3) and women (n = 6) aged ≥18. Data from the FGD were coded and thematic analysis conducted. We found that elderly women seem to have a central advisory role with respect to maternal and child nutrition and that men and elderly women upheld patriarchal gender divisions of labour, which entrust mothers with the primarily responsibility for young children's nutrition. Young mothers relied on elderly women for provision of childcare and nutritious foods for children; however, they demonstrated some resistance to traditionally feminized forms of food preparation. We found that men's involvement in children's nutrition was limited, though they expressed a preference to be more involved in maternal and child nutrition and care practices. A gender transformative approach to policy development, which includes elderly women and men, has the potential to promote more gender‐equitable nutrition practices, increase young women's self‐efficacy and support them to overcome barriers that could be limiting their decision making power in achieving optimal nutrition for themselves and their children.